Pengaruh kepercayaan media sosial dan promosi terhadap penjualan sepatu akasafootstore Bandung - Hertina, Dede; Sahid, Alwi; Kadiman, Yoga Aidil Bagja (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine the effect of social media trust and promotion on the sale of Akasafootstore shoes. This research method is an associative research, the aim is to find out the relationship between two or more variables, then analyze the data obtained through validity tests, reliability tests, multiple regression analysis tests, and hypothesis testing through t tests. The results of the study state that trust, social media, and promotion have an influence on sales. It is proven that trust, social media, and promotions have a significant effect on sales at Akasafootstore, meaning that very high trust will increase sales, attractive social media can increase sales as well, and promotions are very profitable sales because they can add products so that consumers can buy the product and sales will increase very high.